IMPACT ANALYSIS OF ONE VILLAGE ONE HAFIDZ PROGRAM IN IMPROVING THE QUALITY OF HUMAN RESOURCES IN WEST JAVA - Riny Kusumawati (Al-Mubin, 2023)
One Village One Hafidz Program is a program that aims to motivate the community and create Hafidz in the village, in an effort to realize the Vision of West Java Inner and Outer Champion. The program is in line with the central government's vision to improve the quality of human resources, which not only emphasizes technology and education, but also religious values need to be improved. This study aims to determine the improvement of the quality of human resources through the One Village One Hafidz Program in West Java and to determine the inhibiting and supporting factors of the strategy to improve human resources through the One Village One Hafidz Program. The type of research used in this research is quantitative research. This study describes how the government is improving human resources through the One Village One Hafidz program in West Java. The types of data used are primary data and secondary data. Primary data was obtained through distributing questionnaires to research respondents. The questionnaire is in the form of open and close ended questions distributed via Google Form. While secondary data comes from articles, journals or related literature. The results of data analysis show that all variables tested in this study have a positive and significant effect on program success. The results of the analysis show that the dimensions of awareness building, meeting program needs, leaders support the program, setting program targets and budgets according to scope has the largest loading factor value